EFFECTS OF SOIL PHYSICOCHEMICAL PROPERTIES ON BIODIVERSITY AND DISTRIBUTION OF SOIL INVERTEBRATES (Experimental biology, 2021)
Soil invertebrates are bioindicators that characterize environmental changes due to high ecologicaland species diversity, close contact with the soil, high sensitivity and rapid response to changes inenvironmental parameters. This article presents the results of studies conducted in the biogeocenosesof the foothills of the beyond Ile Alatau in the period from 2018 to 2020. The parameters that affectthe distribution and species composition of earthworms in various biogeocenoses are determined: soilmoisture, organic matter index and pH of the environment. The family Lumbricidae is widely distributedin all biocenoses, although the predominant distribution is in the floodplain meadow. The humuscontent in the soils of this biocenosis is 3.26±0.30%, and the humidity is 14.56±2.58%. As a resultof the study, 8 species of earthworms of the family Lumbricidae were identified, belonging to 5 genera:Octolasium lacteum, Eisenia foetida, Eisenia nordenskioldi, Nicodrilus caliginosus, Nicodrilus longus,Lumbricus rubellus, Lumbricus terrestris, Dendrobaena octaedra. The ratio of invertebrate groups in thesoil varies throughout the season. Earthworms are found in the soils of biogeocenoses from June to September. Changes in environmental conditions contribute not only to the distribution and diversity of soilmesofauna, but also to their seasonal dynamics.Key words: soil mesofauna, earthworm, foothills of the beyond Ile Alatau, biogeocenosis, physical and chemical parameters.